Using Various Skin Graft Techniques in Major Burn Reconstruction: A Lesson Learned From a Taiwanese Cornstarch Explosion. (February 2021) - Wu, Chang-Ju; Li, Jung-Jie; Liao, Wen-Chieh; Wang, Tien-Hsiang; Perng, Cherng-Kang; Ma, Hsu; Shih, Yu-Chung; Chen, Mei-Chun; Lin, Chih-Hsun
Abstract : Purpose: Four hundred and ninety-nine patients had burn injuries in an explosion in Taiwan on June 27, 2015, 24 were admitted to the intensive care units of Taipei Veterans General Hospital. This study details our experience with surgical management of these patients, focusing primarily on various skin graft techniques. Materials and Methods: This single-center retrospective study included patients who underwent at least one of the previously mentioned skin graft techniques because of extensive skin defects. The demography, burn diagram, treatment modalities, postoperative outcome, and costs were all analyzed, and a comparison with traditional mesh skin grafts was performed. The literature was also reviewed. Results: Fourteen patients underwent the Meek skin graft technique. Only 3 received ReCell and 1 cultured epithelial autograft (CEA) at separate time point. Overall, the autologous skin grafts, including Meek/ReCell/CEA were completed within 6 months. The average skin graft success rate was approximately 72.9%, 79.2%, and 38% in Meek, ReCell, and CEA, respectively. The infection rate was approximately 35.7%, 25%, and 100% in Meek, ReCell, and CEA, respectively. The average surgical cost and total medical cost were significantly higher in patients who underwent Meek/ReCell/CEA treatments. Conclusions: In our experience, Meek and ReCell treatments had acceptable success rates, but CEA treatment not. ReCell and CEA treatments are useful in the event of extremely limited donor sites, and they are fragile, easily infected, and technically challenging. These techniques also require longer hospitalization and tend to be more expensive, all factors that should be considered when assessing treatment options.